Characterisation of the rat oesophagus epithelium antigens defined by the so-called 'antikeratin antibodies', specific for rheumatoid arthritis. Issue 10 (October 1993) - Girbal, E; Sebbag, M; Gomès-Daudrix, V; Simon, M; Vincent, C; Serre, G
Abstract : OBJECTIVES--An attempt was made to characterise the antigens recognised by serum IgG antibodies directed to the stratum corneum of rat oesophagus epithelium, the so-called 'antikeratin antibodies', which were shown to be highly specific for rheumatoid arthritis (RA) and thus to have an actual diagnostic value. METHODS--Immunoblotting was performed with RA serum samples on different extracts of rat oesophagus epithelium separated by various monodimensional and two dimensional electrophoreses. RESULTS--Three low-salt-soluble antigens sensitive to proteinase K and, therefore, of protein nature were identified. Two proteins, with apparent molecular masses of 210 and 120-90 kilodaltons, shared isoelectric points ranging from 5.8 to 8.5; the third protein exhibited isoelectric points from 4.5 to 7.2 while its molecular mass ranged from 130 to 60 kilodaltons. Immunoadsorption of RA serum samples onto cytokeratins extracted from the stratum corneum of rat oesophagus epithelium did not change their immunoreactivity towards the three antigenic proteins. Widely used deglycosylation and dephosphorylation methods failed to modify either the electrophoretic migration of the proteins or their immunoreactivity with RA serum samples. CONCLUSION--The so-called 'antikeratin antibodies' do not react with cytokeratins. They specifically recognise three late epithelial differentiation proteins which had not been previously described. These proteins may be related to (pro)filaggrin.